Report : dancing between diversity and consistency : refining assessment in postgraduate degrees in dance. - Phillips, Maggi; Stock, Cheryl; Vincs, Kim (Australian Learning and Teaching Council (ALTC), 2008)
Report from a research project that investigated key issues and challenges in developing flexible guidelines for best practice in Australian Doctoral and Masters by Research Examination, encompassing the two modes of investigation, written and multi-modal (practice-led/based) theses, their distinctiveness and their potential interplay. The report is a contextual document accompanying the main outcome of the study which is a booklet titled, Dancing Between Diversity and Consistency: Refining Assessment in Postgraduate Degrees in Dance. Covered here are the nuts and bolts of the project: its initiation, methodological development, outcomes, limitations and successes, at least as can be evaluated at this point of launching the guidelines and discussion papers.